A novel adaptive congestion-aware and load-balanced routing algorithm in networks-on-chip. (October 2018) - Akbar, Reza; Safaei, Farshad; Khodadad, Ehsan
Abstract: Congestion-aware routing algorithms attempt to have more diversity in routes to be chosen and avoid congested areas in networks-on-chip. In this paper, a novel fully adaptive congestion-aware routing algorithm called zigzag routing algorithm (ZRA) along with a new load-balanced method is proposed. ZRA presents a new way for transmitting congestion information, which allows a better view on congestion compared to other algorithms. Furthermore, the load-balanced method recognizes a forbidden area in the network according to betweenness centrality parameter. Fortifying ZRA with this novel load-balanced scheme yields more improvement in performance compared with the previous work. On average, we have accomplished 20.8% and 12.4% improvement in SPLASH-2 benchmark in contrast to DyAD and CATRA algorithms, respectively. It can be claimed that the proposed routing scheme does not consume more power than DyAD and CATRA. Moreover, a new parameter is suggested for comparing load-balanced algorithms, called the variance of crossbar activity.